CERAMIC “FRUIT-STANDS” FROM THE EARLY BRONZE AGE SITES OF COASTAL DAGESTAN - Budajciev, Arsen Lahmanovic (History, Archeology and Ethnography of the Caucasus, 2023)
Vases constitute a distinct category of ceramic ware discovered at Early Bronze Age sites in Coastal Dagestan. In domestic studies, these vessels have not yet been sufficiently covered. In foreign archaeological literature, this type of vessels on tall hollow stems is conventionally referred to as “fruit-stands”. The article explores the typology of ceramic vases from the burial grounds of Velikent I (Catacomb 8) and III (Catacomb 1), Kayakent VI, and the Torpakh-kala settlement. It delves into aspects such as their decoration, purpose, chronology, and origin. A total of seven vases (excluding fragments) were identified across the mentioned sites, each possessing distinctive features. During this period, vases were not as common as other types of ordinary ceramic tableware and are notably absent in the archaeological sites of the mountain and foothill regions of Dagestan. Analogies to these vases in Dagestan are recorded in sites from Northeast Azerbaijan (e.g., Serkertepe settlement, Garachay burial ground etc.) as well as in sites of Central and Eastern Anatolia, Northwestern Iran, and other regions. The abundance and size variety of “fruit-stands”, previously classified as ritual vessels, on Late Chalcolithic sites in Anatolia suggests a regional origin for this ceramic tradition. In the East Caucasus region, these vessels emerge in the early 3rd millennium BC and persist until the middle of the 3rd millennium BC.